Reforming pensions in Europe: a comparative country analysis - Natali, David; Stamati, Furio (Brussels, 2013)
"This working paper assesses the impact of the economic crisis on European pension systems and provides a comparative overview of the measures imposed on European pension systems, together with their effects.